Free solo [videorecording (DVD)] - Chin, Jimmy; Chin, Jimmy; Chin, Jimmy; Vasarhelyi, Elizabeth Chai; Vasarhelyi, Elizabeth Chai; Caldwell, Tommy; Honnold, Alex; McCandless, Sanni (National Geographic, 2019)
Follows free solo climber Alex Honnold, as he prepares mentally and physically to climb the 3200-foot El Capitan in Yosemite without a rope or safety gear.